2000
DOI: 10.1161/01.str.31.9.2074
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Stroke Incidence and Survival in 3 Areas of Europe

Abstract: Background and Purpose-Comparison of incidence and case-fatality rates for stroke in different countries may increase our understanding of the etiology of the disease, its natural history, and management. Within the context of an aging population and the trend for governments to set targets to reduce stroke risk and death from stroke, prospective comparison of such data across countries may identify what drives the variation in risk and outcome. Methods-Population-based stroke registers, using multiple sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
68
2
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 14 publications
(16 reference statements)
18
68
2
9
Order By: Relevance
“…Similar rates were reported from the European Registries of Stroke Collaboration in which 1-month mortality after stroke ranged from 13 to 27% 26 . While a lower rates of 13% were observed by Yahalom and colleagues.…”
supporting
confidence: 83%
“…Similar rates were reported from the European Registries of Stroke Collaboration in which 1-month mortality after stroke ranged from 13 to 27% 26 . While a lower rates of 13% were observed by Yahalom and colleagues.…”
supporting
confidence: 83%
“…10,12,17,18 Results in IS mainly contributed to relatively high age-adjusted incidence rates for FES in our study (1.25 95% CI 1.14 to 1.35; Erlangen: 1.06 95% CI 0.95 to 1.16; South London: 0.86 95% CI 0.79 to 0.93; Dijon: 0.87 95% CI 0.79 to 0.92). 17 A recent comparative study also showed that variations in stroke incidence between different European regions were mainly related to differences in incidence of IS.…”
Section: Discussionmentioning
confidence: 47%
“…10,12,17,18 Results in IS mainly contributed to relatively high age-adjusted incidence rates for FES in our study (1.25 95% CI 1.14 to 1.35; Erlangen: 1.06 95% CI 0.95 to 1.16; South London: 0.86 95% CI 0.79 to 0.93; Dijon: 0.87 95% CI 0.79 to 0.92). 17 A recent comparative study also showed that variations in stroke incidence between different European regions were mainly related to differences in incidence of IS. 16 Crude case-fatality rates for FES were clearly lower than those reported by the German stroke register from Erlangen approximately 10 years ago (13 10,18 As mentioned, we found higher incidence rates mainly in younger patients with stroke, a group of patients with usually lower mortality rates after stroke.…”
Section: Discussionmentioning
confidence: 47%
“…The rate adjusted to the European population in our study (151/100 000) is high compared with that of continental France (100/100 000). 30 However, such comparison is not as valid as one from a biracial cohort because these 2 populations differ not only in ethnicity but also in a number of environmental factors, including climate, alimentation, and cultural customs. If we nevertheless use French data as the baseline category, the adjusted incidence rate ratio of Martinican to French is 1.6.…”
Section: Discussionmentioning
confidence: 99%